Educational attention with the Deaf Community: inputs for professional development, Universidad de Costa Rica - Ovares Fernández, Yanúa (2025)
This academic essay aims to explore the dynamics of educational offers and services at the national level. Also explore the situations that have influenced the education of the deaf person. At the same time, it examines how the University of Costa Rica (UCR), through the Special Education program from the high school and undergraduate levels, has attempted to respond to the needs of the context. Through documentary review and interviews with 10 people from the deaf community, we observe the support that has been generated at the university training level. This analysis shows the efforts of the Ministry of Public Education (MEP) to support the education of deaf people through different services. The experiences of the deaf community people, as well as the different educational services from the MEP, show that it is necessary to strengthen the vocational training process to respond to current demands with an increasingly diverse population. From UCR is necessary review the bachelor’s degree program to respond to reality of deaf student. Finally, is important stablish training program to support teacher's skills for deaf students.